“The Legend of Balinese Goddesses”: Komodifikasi Seni Pertunjukan Hibrid dalam Pariwisata Bali - Gede Suardana; I Nyoman Darma Putra; Nengah Bawa Atmaja (Jurnal Kajian Bali (Journal of Bali Studies), 2018)
This article examines the commodification of hybrid performing arts in Bali tourism, especially the “Bali Agung - The Legend of Balinese Goddesses” performed regularly at Bali Safari and Marine Park, Gianyar. Data were collected by observation techniques, interviews, and literature review, then discussed with commodity theory and cultural tourism ideology.The study shos that hybridity in this performance is evident from the blended of cultural elements of Bali, China, and Western technology. Hybrid tourism performing arts produced can be communal and institutional in ownership. The hybrid tourism performing art is communal because it is created without copyright so it belongs to the people of Bali, while the hybrid performing arts is institutional because it is created with copyright so that ownership and pro t is only enjoyed by the industry that ‘recreated dan performed’ it. Although di erent, communal and institutional hybrid tourism performing arts have been able to become arts that give new color to the rich variety of Balinese art and culture.